Conditional optimization mathematical model of the asphalt concrete mixture grading - Sivilevičius, Henrikas; Podviezko, Valentinas (Journal of Civil Engineering and Management, 2002)
A new partial conditional optimization method which enables to select the best ratio of imported fillers not only while designing the composition of asphalt concrete mixture but also while adjusting the composition of the produced asphalt concrete mixture according to the actual quality of hot fractions is presented. The constructed mathematical model, algorithm and the solved task prove that irrespective of the number of fillers (from 2 to 7 and more) the ratio of their mass can be selected which enables to produce an asphalt concrete mixture which meets the requirements of the composition project best. The mass ratio λ of imported fillers A1 and reclaimed dust A2, which settled and accumulated in the dry purification equipment of an asphalt concrete plant presented in Regulations DAT.AD-96 was taken into account for the first time. Methodological scientific novelty and a possibility to apply it in practice can improve the control of asphalt concrete mixture production. Frist Published Online: 30 Jul 2012